Evaluating Evidence-Based Student Development for School Counseling Program Enhancement - Lakadjo, Mohamad Awal; Sari, Permata; Pautina, Mohamad Rizal; Salam Tuasikal, Jumadi Mori (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
This study aims to evaluate the level of developmental achievement of high school students in Gorontalo City, focusing on developmental dimensions according to the Student Independence Competency Standards. The study used a survey method with the Developmental Task Inventory instrument to measure dimensions such as ethical behavior foundation, emotional maturity, economic independence, and career preparation. The results showed that several aspects of development, such as intellectual maturity and career awareness, had good achievements. In contrast, ethical behavior, responsibility, and self-acceptance require special attention. These findings provide a basis for developing evidence-based school counseling programs to support student development holistically. Limitations of the study related to the scope of the area and quantitative approach were identified, with recommendations for further research covering a wider area and a mixed-method approach.